Where athletes in the Premier League, the N.B.A. and other sports leagues come from, in 15 charts - Aisch, G.; Quealy, K.; Smith, R. (New York Times, 2018)
In 2018, most of the top professional sports leagues in North America and Europe will share an important trait: They will be more international in composition than ever before.